"L'uom che di veder tanto desio". Sulle tracce dei (mancati) rapporti fra Ariosto e Sannazaro (Quaderni di Gargnano, 2020)
When Ariosto started writing poetry, the eighteen-years-older Sannazaro had already gained wide recognition as the author of the Arcadia. Since then, the careers of the two poets were to develop in parallel, but no real mutual exchange took place between each other. While this may sound obvious in the case of the Neapolitan writer, who early in the XVI century turned entirely to Humanism, Ariosto’s apparent lack of interest in Sannazaro’s works is, conversely, a point that deserves attention. This contribute aims to determine the actual extent to which Sannazaro’s lesson was absorbed and reacted to by Ariosto, some of whose poetical choices may thus become clearer. To this end, a number of relevant passages of the Orlando furioso and of the Rime will be considered, and the role of Bembo as a possible mediator for Ariosto’s reception of Sannazaro will be also discussed.  Questo articolo si interroga sulle possibili influenze letterarie di Sannazaro su Ariosto, argomento che non è stato finora esplorato dagli studiosi. Nonostante Ariosto conoscesse senz’altro l’opera del maestro napoletano, questa non sembra aver lasciato una traccia significativa né sul Furioso, né sul corpus lirico. È il caso di approfondire le ragioni di questo distacco, che può essere dovuto sia a una sostanziale differenza di approccio ai generi letterari, sia alla volontà ariostesca di rivendicare un terreno personale e nuovo. Si passerà poi a esaminare i pochi casi dove sembra verificarsi una vera e propria ripresa, o un’affinità nella gestione della sintassi poetica, per comprendere quale valore avesse per Ariosto l’insegnamento sannazariano.
Keywords: Sannazaro; Sonetti et canzoni; Ariosto; Orlando furioso; Rime ariostesche